Catalyst-free efficient synthesis of 2-aminothiazoles in water at ambient temperature - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Tetrahedron, 2008)
A highly efficient and facile method has been described for the synthesis of substituted 2-aminothiazoles in water without any added catalyst or co-organic solvent. The reaction was carried out at ambient temperature and the products were obtained in excellent isolated yields. The developed protocol is successfully applied for the preparation of an anti-inflammatory drug, fanetizole. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 2-aminothiazoles; ambient temperature; environment-friendly synthesis; Water